A detailed analysis of the spatial distribution of Schöningen 13II-4 'Spear Horizon' faunal remains. Issue 152 (March 2021) - García-Moreno, Alejandro; Hutson, Jarod M.; Villaluenga, Aritza; Turner, Elaine; Gaudzinski-Windheuser, Sabine
Abstract: The Middle Pleistocene Schöningen 13II-4 'Spear Horizon' (Germany) is a key site for the study of human evolution, most notably for the discovery of Paleolithic wooden weaponry and evidence for developed hunting strategies. On the other hand, the 'Spear Horizon' offers an excellent opportunity to approach hominin spatial behavior, thanks to the richness of the archeological assemblage, its exceptional preservation, and the vast expanse of the excavated surface. Analyzing how space was used is essential for understanding hominin behavior at this unique open-air site and, from a wider perspective, for approaching how humans adapted to interglacial environments. In this article, we present an exhaustive spatial study of the complete Schöningen 13II-4 'Spear Horizon' faunal assemblage and its archeological context, combining zooarcheology and spatial analysis through the extensive application of geographic information systems. Our results indicate the existence of different activity areas related to changes in the position of the shoreline due to fluctuations of water table levels of the Schöningen paleolake. These activity areas were likely used on a seasonal basis, whereas the spatial patterning observed in the distribution of faunal remains suggests a diversity of behavioral strategies in terms of intensity and/or duration of occupations. This study refines previous interpretations of the site and reconstructs human behavioral adaptations and the occupational changing lakeland environment during the Middle Pleistocene in Europe. Highlights: We conducted a detailed spatial analysis of the Schöningen 13II-4 faunal assemblage. We documented different activity areas related to changes in water table levels. We propose a seasonal pattern for human occupations at Schöningen 13II-4. Schöningen 13II-4 can be used as a model for open-air sites during Middle Pleistocene. We extensively applied GIS to Palaeolithic intrasite spatial archeology.